Utilization Of Cashew Nut Seeds For Liquid Smoke Production Using The Pyrolysis Method - Jayanegara, Sudarmanto; Alqadri, A. Imam Ramdhana; Mandasini, Mandasini; Sayudi, Chayping Mardi; La Ifa, La Ifa (Journal of Science and Engineering, 2025)
Waste biomass is increasingly growingly and will be environmental pollution if not used wisely, this waste can be processed into fuel alternatives, in addition to the smoke from burning waste can be used as liquid smoke, as fertilizers and preservatives, both textile and food. This study aimed to determine the effect of time and temperature of the liquid smoke results from nut shells. Total sampel of research as 1500gr using pyrolysis method. Pyrolysis process is carried out at a temperature pyrolysis reactor 150-450oC. The production of liquid smoke from shell nut 1500gr by the method of pyrolysis produces liquid smoke grade 3 with the results of the best liquid at a temperature of 450oC and the optimum time of 2,5 hours at a yield of 32,66%. From the analysis using GC-MC spectrophotometer produces major chemical component of phenols(36,310%), acid(12,9475%) and carbonyl(16,715%).